2011
DOI: 10.1080/19440049.2011.604644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of migration from polyethersulphone and polycarbonate baby bottles

Abstract: This work presents two analytical methods developed for measuring three components of polyethersulphone (PES) and applying them to the migration testing of 30 baby bottles made of PES. The study also provides migration results under the same conditions for bisphenol A (BPA) from 40 polycarbonate baby bottles using a well-established method adapted to low concentrations. For PES bottles, migration of diphenyl sulphone (DPS), 4,4'-dichlorodiphenyl sulphone (DCPS) and 4,4'-dihydroxydiphenyl sulphone (DHPS; also k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 10 publications
3
40
0
2
Order By: Relevance
“…A team led by Catherine Simoneau of the Institute for Health and Consumer Protection analysed a total of 30 BPS-containing baby bottles from 12 countries. After five minutes in boiling water and two hours at 70 °C, none of the bottles released detectable quantities of BPS 5 . "These materials are far more resistant to hydrolytic breakdown than polycarbonate -that was one of the big selling points, " says Schmidt.…”
Section: A Key To Actionmentioning
confidence: 99%
“…A team led by Catherine Simoneau of the Institute for Health and Consumer Protection analysed a total of 30 BPS-containing baby bottles from 12 countries. After five minutes in boiling water and two hours at 70 °C, none of the bottles released detectable quantities of BPS 5 . "These materials are far more resistant to hydrolytic breakdown than polycarbonate -that was one of the big selling points, " says Schmidt.…”
Section: A Key To Actionmentioning
confidence: 99%
“…Earlier studies have shown that BPA can leach from polycarbonate drinking and baby bottles or from metallic-can epoxy coatings into various food products (Cao & Corriveau 2008;Cao et al 2009;Cooper et al 2011;Simoneau et al 2011). Heat processing or acidic conditions can enhance the leaching of BPA from packaging materials or storage containers (Munguia-Lopez & Soto-Valdez 2001;Munguia-Lopez et al 2002;Lim et al 2009).…”
Section: Please Scroll Down For Articlementioning
confidence: 97%
“…BPF and BPS are present in food-packaging materials and paper products (Liao and Kannan, 2013;Liao et al, 2012b). Furthermore, BPS is considered a safe alternative for BPA in the manufacture of plastic infant feeding bottles (Simoneau et al, 2011). Regrettably, there are limited data regarding the toxic effects of these bipshenols (BPs), mostly from in vitro studies.…”
Section: Introductionmentioning
confidence: 99%